CONSUMER PSYCHOLOGY AS A RELIGIOUS TOURISM MARKETING STRATEGY - Maghfur, Arif (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2024)
Tourism is a global industry sector that has great potential to be developed as a source of income. One of the tourism that is widely spread in Indonesia, especially the island of Java, is religious tourism. From various regions it seems to flock to visit this tourism. The visit from the tourists is able to contribute to the economy of the area. Therefore, this needs special attention. In determining tourism, tourists experience a psychological process from the period of a person's travel to the psychological condition during the activity until after the tourism activity is completed. Consumer psychological studies can explain the psychological processes experienced by tourists through internal, external and situational factors. These three factors affect marketing strategies, namely market segmentation, product, positioning and marketing mix. This study will explain how consumer psychology in tourism works.